Air pollution in the Aveiro Region, Portugal: a citizens’ engagement approach - Coelho, Sílvia (2019)
Air pollution has become a growing concern in the past few years, with an increasing number of acute air pollution episodes in many cities worldwide. In Portugal, especially in the region of Aveiro, high concentrations of particulate matter are frequently recorded, being one of the most critical air pollutants. Health impacts related with citizens’ exposure to particulate matter has been threatening human health, increasing mortality and morbidity and contributing to a broad range of negative health outcomes. Different causes are attributed to air pollution over Portugal: agricultural, forest fires and dust emissions from Sahara Desert, amongst the natural emission sources, and road-traffic, residential combustion and industrial emissions, amongst the anthropogenic emission sources. Citizens’ behaviour has a main role on air quality management. Each day individual choices, such as transportation or residential heating, have direct impact on air pollutant emissions. Therefore, citizens’ play an important role to mitigate air pollution problems in their cities. However, the first step is to increase citizens’ receptiveness about their contribution to the problem and, at the same time, to engage and empower them to contribute to the solutions. Aveiro Region is one of the case studies of ClairCity (Citizen-led air pollution reduction in cities) project. The project developed several activities to engage citizens on air pollution and carbon emissions issues. This work focus on the Delphi-like approach that includes surveys and workshops, to find out about people’s lives in Aveiro Region and their vision for a low carbon, clean air and healthy future region. This paper presents an overview about air pollution in Aveiro region as well as the activities of the Delphi survey to see how citizens perceive this problem and their role on future air quality management.